Smaller birth size may be associated with lower physical activity in adult women - Kinga Słojewska; Andrzej Galbarczyk; Magdalena Klimek; Magdalena Mijas; Anna Tubek-Krokosz; Karolina Krzych-Miłkowska; Monika Ścibor; Grazyna Jasienska (Scientific Reports)
Abstract Conditions during fetal development are crucial for a long-term health. Individuals with small size at birth are suggested to have energy-thrifty physiology, a tendency to conserve energy due to adaptations to undernutrition during early development. However, energy also could be saved by having low physical activity. We hypothesize that individuals born smaller are less physically active compared to those born larger. Data were collected from 136 healthy, urban women (mean age 26.6, SD 4.24) over 3 consecutive menstrual cycles. Cycle 1 involved usual physical activity, while in cycles 2 and 3 women were instructed to perform at least 180 min/week of moderate to vigorous activity. Birth weight and length were obtained from personal medical records, and physical activity was monitored using a Fitbit wristband accelerometers. For each woman, ponderal index (indicator of leanness at birth) was calculated. Smaller size at birth predicted lower total energy expenditure during adulthood. The ponderal index was positively associated with duration of vigorous physical activity across all cycles (cycle 1: p < 0.001; cycle 2: p = 0.011; cycle 3: p = 0.004), while the birth weight was positively related to total energy expenditure (cycle 1: p = 0.014; cycle 2: p = 0.008; cycle 3: p = 0.016). Fetal developmental conditions might be associated with physical activity levels in later life. Women born smaller have lower total energy expenditure and are less likely to engage in vigorous activity. These findings underscore the role of early life factors in shaping health-related behaviors and suggest that individuals born with smaller size may need additional support or tailored interventions to meet the recommended levels of physical activity.